2016
DOI: 10.14689/ejer.2016.63.11
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Differentiated Teaching Approach in the Algebraic Learning Field on Students' Academic Achievements

Abstract: Suggested Citation:Bal, A. P. (2016). The effect of the differentiated teaching approach in the algebraic learning field on students' academic achievements.Eurasian Journal of Educational Research, 63, 185-204, http://dx.doi.org/ 10.14689/ejer.2016.63.11 AbstractProblem Statement: Algebra, which is one of the basic principles of mathematical learning, still maintains its importance in mathematics programmes. However, especially starting from the primary school years, algebra represents a complex mathematical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 7 publications
(15 reference statements)
5
31
0
6
Order By: Relevance
“…In Table 2, the characteristics and individual effects of the studies included in our review are summarized. The selection of studies includes eight quasi-experimental studies in which classes were randomly allocated to a control or experimental condition (Mastropieri et al, 2006; Richards and Omdal, 2007; Huber et al, 2009; Vogt and Rogalla, 2009; Little et al, 2014; Altintas and Özdemir, 2015a,b; Bal, 2016; Bhagat et al, 2016), three studies in which schools were randomly allocated to conditions (Wambugu and Changeiywo, 2008; Mitee and Obaitan, 2015; Bikić et al, 2016), and one survey-study (Smit and Humpert, 2012). These studies covered a wide range of academic subjects, including science, mathematics and reading.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Table 2, the characteristics and individual effects of the studies included in our review are summarized. The selection of studies includes eight quasi-experimental studies in which classes were randomly allocated to a control or experimental condition (Mastropieri et al, 2006; Richards and Omdal, 2007; Huber et al, 2009; Vogt and Rogalla, 2009; Little et al, 2014; Altintas and Özdemir, 2015a,b; Bal, 2016; Bhagat et al, 2016), three studies in which schools were randomly allocated to conditions (Wambugu and Changeiywo, 2008; Mitee and Obaitan, 2015; Bikić et al, 2016), and one survey-study (Smit and Humpert, 2012). These studies covered a wide range of academic subjects, including science, mathematics and reading.…”
Section: Resultsmentioning
confidence: 99%
“…Note that the it seems that the pretest-scores of the grade 7 students were non-normally distributed (since the authors use a non-parametric test) and also the pre-test scores are not provided. The combined effect of these two subgroups was calculated in CMA (using study as the unit of analysis) .B For our analyses, we used information from the ANCOVA in Table 4 of the paper of Bal (2016) to calculate a correlation and used this in CMA to calculate Cohen's d. Note that the values are from an ANCOVA, implying they may be positively biased .C For our analyses, we used means of the subgroups in the classes from Table 3 from the paper of Bhagat et al (2016) to calculate an overall effect (using study as the unit of analysis). The pretest and posttest consisted of the same items but in a different order.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, several studies have shown that the implementation of DI has a positive impact on students' school performance in general (Valiandes 2015;Tulbure 2011). It also has positive effects on reading (Goddard, Goddard, and Minjung 2015;Firmender, Reis, and Sweeny 2013;Reis et al 2011) and mathematical performance (Bal 2016;Goddard, Goddard, and Minjung 2015). The use of DI also has a positive effect on student performance, on enhancing student commitment, interests, satisfaction (Johnsen 2003) and their self-confidence (McQuarrie and McRae 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature on teachers’ use of inclusive teaching practices has shown several positive outcomes, for example, the influence of differentiated instruction on academic performance (e.g., Bal, 2016; Valiandes, 2015); in this vein, Knauder and Koschmieder (2019) identified teachers’ self‐efficacy beliefs and teachers’ attitudes as key influencing factors of individualised teaching. Hence, it seems important to examine the factors influencing teachers’ appropriate use of inclusive teaching practices.…”
Section: Introductionmentioning
confidence: 99%